Floating correspondences: the butoh and women's voice in Abya Yala (Urdimento: Revista de Estudos em Artes Cênicas, 2020)
This article expands on the electronics correspondences exchanged with the butoh dancers Eugenia Vargas (Mexico) and Susana Reyes (Ecuador) in the midst of the worldwide coronavirus pandemic crisis.Concerns shared with the artists sought to foment self-reflections about their practices in the butoh, which are analyzed here from a theoretical interweaving inscribed in the Abya Yala-Japan transit.The approach pursues clues that allow organizing a set of ideas about the qualities and powers of the body, worked on by both, and reflecting it as a possible hypothesis evidenced by the exchange of letters. The findings corroborate the body as an expressive, intimate and mythopoetic generating place, seen as personal dance, experienced and woven from relationships that the artists establish with their own culture and ancestry in the face of foreign information.
Keywords: Butoh; Personal dance; Female mythopoetic; Memory; Coronavirus